First, simplify all the individual exponent terms using this rule of exponents:
#(x^color(red)(a))^color(blue)(b) = x^(color(red)(a) xx color(blue)(b))#
#(4(x^color(red)(2))^color(blue)(3)(y^color(red)(4))^color(blue)(2))/(2(x^color(red)(2))^color(blue)(2)(y^color(red)(2))^color(blue)(4)) => (4x^(color(red)(2) xx color(blue)(3))y^(color(red)(4) xx color(blue)(2)))/(2x^(color(red)(2) xx color(blue)(2))y^(color(red)(2) xx color(blue)(4))) = (4x^6y^8)/(2x^4y^8)#
We can now rewrite this expression as:
#4/2(x^6/x^4)(y^8/y^8) => 2(x^6/x^4)1 => 2(x^6/x^4)#
We can now use this rule of exponents to complete the simplification of the #x# terms:
#x^color(red)(a)/x^color(blue)(b) = x^(color(red)(a)-color(blue)(b))#
#2(x^color(red)(6)/x^color(blue)(4)) => 2x^(color(red)(6)-color(blue)(4)) =>#
#2x^2#